A new species of Heliocephala from Vietnam - Mel'nik, Vadim A. (2013)
Heliocephala vietnamensis sp. nov., a hyphomycetous fungus collected on decaying leaves of an unidentified plant, is described and illustrated. It is distinguished by determinate apical cluster of conidiogenous cells and obclavate to sub-navicular, 3-septate, pale brown conidia.